The Effect of YouTube Videos in Improving Students' Listening Skill - Ameliya Ramadhani Andi; Sukardi Weda; Sahril (International Journal of Language, Education, and Literature, 2025)
YouTube is a website where people around the world share various kinds of videos. Videos from YouTube are proven to be able to attract students’ interest in learning English because they provide audio and visual. Furthermore, this research aims to find out whether YouTube videos can improve students' listening skills in learning recount text and also the strengths and weaknesses of learning listening using YouTube videos in the classroom. This is a quasi-experimental research, more precisely pre-test and post-test with non-equivalent control-group design. The population of this research is tenth grade students of SMKN 2 Bone in the 2023/2024 academic year. The results of this study showed that: 1) The t-test is higher than the t-table, which is 3.304 > 2.018 means the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. It was concluded that the use of YouTube videos in the classroom was effective in improving students' listening skills in learning recount text; 2) The strength of learning listening in the classroom using YouTube videos, namely, it can train students' listening skills, provide a pleasant learning atmosphere, attract students' attention with varied videos, increase students' involvement, and increase students' knowledge of English.